Preparation method and application of sodium ion battery negative electrode material
Cerium titanate was prepared by mixed ball milling of cerium, titanium and polar solvents, and boron fluoride was added and carbon source was added to form a carbon-coated cerium titanium titanate-titanium niobate heterojunction negative electrode material co-doped with boron fluorine, which solved the problems of poor conductivity and cycle stability of the existing sodium ion battery negative electrode materials, and achieved excellent rate performance and capacity retention.
Patent Information
- Application Number
- CN202510315314.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The negative electrode materials of existing sodium ion battery have poor conductivity and poor cycle stability, resulting in low rate performance and cycle stability, making it difficult to meet the requirements of commercial applications.
Cerium titanate was prepared by mixed ball milling method of cerium, titanium and polar solvents, followed by addition of boron fluoride and carbon source, and heterojunction was formed by spray drying and Joule thermal shock, and finally carbon coating was carried out under a protective atmosphere to obtain a cerium titanium titanium niobate heterojunction negative electrode material co-doped with boron fluorine.
The conductivity and cyclic stability of the negative electrode material of sodium ion battery are significantly improved, the rate performance and capacity retention rate are improved. After cycling for 200 cycles at a current density of 0.5A/g, the capacitance value remains at 84-88% of the initial value.
Smart Images

Figure CN119841350A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of negative electrode materials for sodium ion batteries, and specifically relates to a preparation method and application of negative electrode materials for sodium ion batteries. Background Art
[0002] In recent years, people have begun to pay attention to renewable clean energy such as solar energy, wind energy, and tidal energy. As a popular research direction of secondary batteries, sodium-ion batteries have many characteristics and unique advantages comparable to lithium-ion batteries. The negative electrode material plays an important role in loading and releasing sodium ions, which directly affects the overall kinetic performance of the battery, such as rate performance, power density, etc.
[0003] Metal compound materials have the advantages of high theoretical capacity, suitable sodium storage voltage, good safety and low price. Multi-metal compounds are mainly concentrated in titanium-based compounds. However, the common problems of this type of material are poor conductivity and large volume changes during the cycle, so as negative electrode materials for sodium ion batteries, they often show poor rate performance and cycle stability. In order to improve this problem, non-metal doping, preparation of carbon composites, interface engineering and micro-nanostructured metal compounds are usually used to accelerate charge transfer and improve battery performance.
[0004] The Chinese patent document with publication number CN106784773A discloses a method for preparing an electrode material, firstly, a titanium source and a niobium source are mixed and transferred to a crucible, and then heat treated to obtain a titanium niobate precursor, and then subjected to high-energy ball milling to obtain a TiNb2O7 material. This method is modified by adding iodine element during the high-energy ball milling process. The electrochemical performance diagram shows that the specific capacity is only 150-180 mAh / g at a current density of 15 mA / g, which is relatively low.
[0005] The Chinese patent document with publication number CN114242995A discloses a sodium ion battery nanosheet negative electrode material and its preparation method and application. First, potassium salt, titanium oxide and niobium oxide are subjected to solid phase sintering, ion exchange and liquid phase stripping to obtain an electronegative TiNbO5 nanosheet dispersion; then, a TiNbO5 / graphene nanosheet heterostructure is formed by electrostatic self-assembly with an electropositive graphene suspension, and the sodium ion battery nanosheet negative electrode material is obtained after freeze-drying. Electrochemical tests have found that the specific capacity at a current density of 0.05A / g is only 247mAh / g, and the first-cycle rate performance is also low, which is not conducive to commercial applications.
[0006] The Chinese patent document with publication number CN117550638A discloses a negative electrode material for a sodium ion battery and a preparation method thereof. Sodium acetate and niobium oxalate are mixed and ball-milled, and the ball-milled mixture is mixed with deionized water and placed in a hydrothermal kettle to form a sol and dry; layered coke is placed in the sol with ethylene glycol as a solvent and heated to obtain a product; the obtained product is naturally cooled and vacuum-dried to obtain a negative electrode material for a sodium ion battery. Due to the low intercalation rate of layered coke in sodium niobate material, the maximum capacity of the assembled battery at a current density of 0.5C is only 205mAh / g, and the capacity decays by 7% in 50 cycles (decays by about 25-30% in 200 cycles, and the retention rate is less than 80%), with poor performance. Summary of the invention
[0007] The purpose of the present invention is to provide a preparation method and application of a negative electrode material for a sodium ion battery. The preparation method is simple, easy to industrialize and can greatly improve the conductivity and cycle stability of the battery.
[0008] In order to achieve the purpose of the present invention, a technical solution for a preparation method of a negative electrode material for a sodium ion battery is provided, comprising the following steps: (1) mixing a cerium source, a titanium source and a polar solvent, ball milling, drying and calcining at high temperature to obtain cerium titanate; (2) mixing the cerium titanate, boron fluoride compound, titanium source, niobium source and alcohol organic solvent obtained in step (1), spray drying to obtain a heterojunction precursor, and subjecting the heterojunction precursor to Joule thermal shock to obtain a boron-fluorine co-doped cerium titanate-titanium niobate heterojunction; (3) adding a carbon source to the boron-fluorine co-doped cerium titanate-titanium niobate heterojunction obtained in step (2), ball milling to obtain a carbon-coated heterojunction precursor, and calcining under a protective atmosphere to obtain a carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction, i.e., a negative electrode material for a sodium ion battery.
[0009] Preferably, in step (1), the cerium source is one of cerium oxide, cerium acetate, and cerium trichloride; the concentration of the cerium source in the polar solvent is 1-2 mol / L; the titanium source is one of titanium dioxide, titanium isopropoxide, and tetrabutyl titanate; the polar solvent is one of methanol, ethanol, and deionized water; and the molar ratio of the cerium source to the titanium source is 1:2-3.
[0010] Preferably, in step (1), the ball milling speed is 300-700 r / min, and the ball milling time is 10-18 h; the drying temperature is 80-120° C., and the time is 10-16 h; the high-temperature calcination is to control the heating rate of 3-10° C. / min to increase the temperature to 900-1450° C., and the insulation time is 12-20 h.
[0011] Preferably, in step (2), the titanium source is one of tetrabutyl titanate, isopropyl titanate, and titanium tetrachloride; the concentration of the titanium source in the alcohol organic solvent is 0.16-0.5 mol / L; the niobium source is one of niobium oxalate, niobium pentachloride, and niobium n-propoxide; the alcohol organic solvent is one of ethanol, methanol, and ethylene glycol; the molar ratio of cerium titanate to titanium niobate is 0.01-0.1:1; the boron fluoride compound is any one of sodium fluoroborate, ammonium fluoroborate, and zinc fluoroborate; and the molar ratio of the boron fluoride compound to titanium niobate is 0.1-1:1.
[0012] Preferably, in step (2), the spray drying feed rate is 3-10 mL / min, the temperature is 150-200° C., and the discharge port temperature is 80-100° C.
[0013] Preferably, in step (2), the Joule thermal shock is performed by heating the sample to 1200-1600° C. within 10-20 seconds under an argon or nitrogen protective gas atmosphere and then keeping the temperature for 5-10 minutes.
[0014] Preferably, in step (3), the carbon source is one of glucose, starch and polymethyl methacrylate; the molar ratio of the carbon source to the weight of titanium niobate is 0.8-2.1:1; the ball milling speed is 1500-2500 r / min, and the ball milling time is 10-30 min. The calcination is carried out under an argon or nitrogen protective gas atmosphere at a heating rate of 2-5 ° C / min to 500-800 ° C, and the holding time is 6-12 h.
[0015] The present invention also provides the application of the prepared sodium ion battery negative electrode material, which is applied to the sodium ion battery.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The preparation method of the negative electrode material of the sodium ion battery provided by the present invention promotes the formation of a heterojunction by inducing and doping with non-metallic ions in a closed reaction environment using a polar solvent. The heterojunction can promote the efficiency of photogenerated electron-hole separation, promote the ion activity of the two interfaces, and improve the electrochemical reaction kinetics.
[0017] 2. The preparation method of the negative electrode material of the sodium ion battery provided by the present invention realizes the co-doping of boron and fluorine by adding boron fluoride. After doping, the band gap of the heterojunction material can be reduced, which is more conducive to the adsorption and desorption of electrolyte ions; non-metallic ion doping can also establish a directional built-in electric field from the inside to the surface of the semiconductor, effectively promoting the migration of photogenerated carriers and improving the rate performance of the battery.
[0018] 3. The preparation method of the negative electrode material of the sodium ion battery provided by the present invention is to quickly synthesize the heterojunction material through a Joule heating furnace. The material after the spray drying equipment is quickly sintered in the Joule heating furnace, which has less damage to the internal bond energy of the material and can synthesize more uniform particles; the traditional tubular furnace has a slow heating speed and a long sintering time, which has a greater impact on the internal structure of the material and can also cause the collapse of the external structure.
[0019] 4. The preparation method of the negative electrode material of the sodium ion battery provided by the present invention can not only stabilize the structure of the heterojunction and ensure that the capacity will not decay rapidly due to volume expansion during a long cycle, but also inhibit the interface reaction between the material surface and the electrolyte, thereby improving the cycle performance.
[0020] 5. The sodium ion battery negative electrode material prepared by the present invention was assembled into a sodium ion battery negative electrode material for electrochemical performance testing. The capacity can reach 271-314 mAh / g at a current density of 0.3A / g, and after 200 cycles at a current density of 0.5A / g, the capacitance value is 84-88% of the initial value. The above data show that the sodium ion battery negative electrode material prepared by the present invention has excellent specific capacity and good cycle stability in the sodium battery negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 C@BF-CeTi prepared in Example 1 21 O 38 SEM spectrum of / TiNb2O7 material; Figure 2 C@BF-CeTi prepared in Comparative Example 1 21 O 38 SEM spectrum of / TiNb2O7 material; Figure 3 C@BF-CeTi prepared in Example 1 21 O 38 / XRD spectrum of TiNb2O7 material; Figure 4 C@BF-CeTi prepared in Example 1 21 O 38 TEM spectrum of / TiNb2O7 material; Figure 5 C@BF-CeTi prepared in Example 1 21 O 38 HRTEM spectrum of / TiNb2O7 material; Figure 6 C@BF-CeTi prepared in Example 1 21 O 38Capacity retention and coulombic efficiency curve of / TiNb2O7 material after 200 cycles at a current density of 0.5A / g. DETAILED DESCRIPTION
[0022] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. Example 1
[0023] (1) 0.04 mol of cerium oxide, 0.02 mol of titanium dioxide and 15 mL of ethanol were ball-milled at 700 r / min for 15 h to obtain a mixture, which was dried at 100 °C for 12 h and then calcined at a high temperature. The calcination parameters were: heating to 1300 °C at 5 °C / min and keeping the temperature for 16 h to obtain cerium titanate; (2) 2 g of cerium titanate, 1 g of zinc fluoroborate, 0.04 mol of tetrabutyl titanate, 0.04 mol of niobium oxalate and 60 mL of ethanol were mixed, and the mixed solution was sprayed quickly through a spray dryer (DC1500) at a peristaltic pump feed rate of 10 mL / min, a nozzle spray temperature of 200 °C, and a discharge port temperature of 80 °C to obtain a heterojunction precursor. The heterojunction precursor was heated to 1600 °C within 10 s and subjected to Joule heat (YLJ-SPS-T20) shock for 5 min. Argon was used as the protective atmosphere to obtain a boron-fluorine co-doped cerium titanate-titanium niobate heterojunction. (3) 0.2 g of polymethyl methacrylate was added to the heterojunction material, and high-energy ball milling was performed at a speed of 2000 r / min for 20 min to obtain a carbon-coated heterojunction precursor. The temperature was raised to 600 °C at a speed of 3 °C / min under an argon protective atmosphere and kept at this temperature for 10 h to obtain a carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction (C@BF-CeTi 21 O 38 / TiNb2O7), which is the negative electrode material of sodium ion battery. Example 2
[0024] (1) 0.02 mol of cerium acetate, 0.03 mol of tetrabutyl titanate and 20 mL of ethanol were ball-milled at a speed of 500 r / min for 17 h to obtain a mixture, which was dried at 80 °C for 16 h and then calcined at a high temperature. The calcination parameters were: heating to 900 °C at 10 °C / min and keeping the temperature for 20 h to obtain cerium titanate; (2) 1 g of cerium titanate, 0.5 g of ammonium fluoroborate, 0.02 mol of titanium tetrachloride, 0.02 mol of niobium pentachloride and 40 mL of methanol were mixed, and the mixed solution was rapidly sprayed out through a spray dryer (DC1500) at a peristaltic pump feed rate of 3 mL / min, a nozzle spray temperature of 180 °C, and a discharge port temperature of 90 °C to obtain a heterojunction precursor. The heterojunction precursor was heated to 1400 °C within 15 s and subjected to Joule heat (YLJ-SPS-T20) shock for 8 min. Nitrogen was used as the protective atmosphere to obtain a boron-fluorine co-doped cerium titanate-titanium niobate heterojunction. (3) 0.4 g of glucose was added to the heterojunction material, and high-energy ball milling was performed at a speed of 1500 r / min for 30 min to obtain a carbon-coated heterojunction precursor. The temperature was raised to 800 °C at a speed of 2 °C / min under a nitrogen protective atmosphere and kept at this temperature for 12 h to obtain a carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction, i.e., a negative electrode material for sodium ion batteries. Example 3
[0025] (1) 0.02 mol of cerium trichloride, 0.04 mol of titanium isopropoxide and 15 mL of deionized water were ball-milled at a speed of 300 r / min for 18 h to obtain a mixture, which was dried at 100 °C for 14 h and then calcined at a high temperature. The calcination parameters were: heating to 1200 °C at 3 °C / min and keeping the temperature for 18 h to obtain cerium titanate; (2) 3 g of cerium titanate, 0.5 g of sodium fluoroborate, 0.01 mol of isopropyl titanate, 0.03 mol of niobium n-propoxide and 60 mL of ethylene glycol were mixed, and the mixed solution was rapidly sprayed out through a spray dryer (DC1500) at a peristaltic pump feed rate of 8 mL / min, a nozzle spray temperature of 160 °C, and a discharge port temperature of 80 °C to obtain a heterojunction precursor. The heterojunction precursor was heated to 1200 °C within 20 s and subjected to Joule heat (YLJ-SPS-T20) shock for 10 min. Nitrogen was used as the protective atmosphere to obtain a boron-fluorine co-doped cerium titanate-titanium niobate heterojunction. (3) 0.1 g starch was added to the heterojunction material, and the product was subjected to high-energy ball milling at a speed of 2500 r / min for 15 min to obtain a carbon-coated heterojunction precursor. The temperature was raised to 500 °C at a rate of 5 °C / min under a nitrogen protective atmosphere and kept at this temperature for 12 h to obtain a carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction, i.e., a negative electrode material for sodium ion batteries. Example 4
[0026] (1) 0.02 mol of cerium acetate, 0.02 mol of titanium dioxide and 10 mL of deionized water were ball-milled at 400 r / min for 10 h to obtain a mixture, which was dried at 120 °C for 10 h and then calcined at high temperature. The calcination parameters were: heating to 1450 °C at 10 °C / min and keeping the temperature for 12 h to obtain cerium titanate; (2) 5 g of cerium titanate, 2 g of ammonium fluoroborate, 0.02 mol of tetrabutyl titanate, 0.04 mol of niobium n-propoxide and 70 mL of methanol were mixed, and the mixed solution was rapidly sprayed out through a spray dryer (DC1500) at a peristaltic pump feed rate of 10 mL / min, a nozzle spray temperature of 150 °C, and a discharge port temperature of 80 °C to obtain a heterojunction precursor. The heterojunction precursor was heated to 1300 °C within 15 s and subjected to Joule heat (YLJ-SPS-T20) shock for 9 min. Argon was used as the protective atmosphere to obtain a boron-fluorine co-doped cerium titanate-titanium niobate heterojunction. (3) 0.3 g of glucose was added to the heterojunction material, and the product was subjected to high-energy ball milling at a speed of 1800 r / min for 25 min to obtain a carbon-coated heterojunction precursor. The temperature was raised to 600 °C at a speed of 4 °C / min under an argon protective atmosphere and kept at this temperature for 8 h to obtain a carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction, i.e., a negative electrode material for sodium ion batteries. Example 5
[0027] (1) 0.04 mol of cerium trichloride, 0.02 mol of titanium dioxide and 20 mL of methanol were ball-milled at 600 r / min for 12 h to obtain a mixture, which was dried at 80 °C for 12 h and then calcined at high temperature. The calcination parameters were: heating to 1000 °C at 5 °C / min and keeping the temperature for 14 h to obtain cerium titanate; (2) 2 g of cerium titanate, 1 g of zinc fluoroborate, 0.01 mol of isopropyl titanate, 0.03 mol of niobium oxalate and 30 mL of ethylene glycol were mixed, and the mixed solution was quickly sprayed out through a spray dryer (DC1500) at a peristaltic pump feed rate of 5 mL / min, a nozzle spray temperature of 180 °C, and a discharge port temperature of 90 °C to obtain a heterojunction precursor. The heterojunction precursor was heated to 1500 °C within 10 s and subjected to Joule heat (YLJ-SPS-T20) shock for 7 min. Argon was used as the protective atmosphere to obtain a boron-fluorine co-doped cerium titanate-titanium niobate heterojunction. (3) Add 0.1 g of polymethyl methacrylate to the heterojunction material, and high-energy ball mill at a speed of 2000 r / min for 10 min to obtain a carbon-coated heterojunction precursor. In an argon protective atmosphere, heat the temperature to 800 °C at a rate of 5 °C / min and keep it for 6 h to obtain a carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction, i.e., the negative electrode material for sodium ion batteries. Example 6
[0028] (1) 0.01 mol of cerium oxide, 0.03 mol of tetrabutyl titanate and 10 mL of methanol were ball-milled at a speed of 500 r / min for 18 h to obtain a mixture, which was dried at 120°C for 12 h and then calcined at a high temperature. The calcination parameters were: heating to 1100°C at 8°C / min and keeping the temperature for 18 h to obtain cerium titanate; (2) 4 g of cerium titanate, 2 g of sodium fluoroborate, 0.02 mol of titanium tetrachloride, 0.04 mol of niobium oxalate and 80 mL of ethanol were mixed, and the mixed solution was quickly sprayed out through a spray dryer (DC1500) at a peristaltic pump feed rate of 10 mL / min, a nozzle spray temperature of 200 °C, and a discharge port temperature of 90 °C to obtain a heterojunction precursor. The heterojunction precursor was heated to 1600 °C within 20 s and subjected to Joule heat (YLJ-SPS-T20) shock for 6 min. Nitrogen was used as the protective atmosphere to obtain a boron-fluorine co-doped cerium titanate-titanium niobate heterojunction; (3) Add 0.5 g starch to the heterojunction material, and high-energy ball mill at a speed of 2000 r / min for 10 min to obtain a carbon-coated heterojunction precursor. Raise the temperature to 700 °C at a rate of 2 °C / min under a nitrogen protective atmosphere and keep the temperature for 10 h to obtain a carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction, i.e., the negative electrode material for sodium ion batteries. Example 7
[0029] (1) 0.04 mol of cerium trichloride, 0.02 mol of tetrabutyl titanate and 20 mL of deionized water were ball-milled at 600 r / min for 12 h to obtain a mixture, which was dried at 100 °C for 16 h and then calcined at high temperature. The calcination parameters were: heating to 1300 °C at 10 °C / min and keeping the temperature for 16 h to obtain cerium titanate; (2) 5 g of cerium titanate, 0.5 g of zinc fluoroborate, 0.02 mol of isopropyl titanate, 0.02 mol of niobium pentachloride and 50 mL of ethylene glycol were mixed, and the mixed solution was rapidly sprayed out through a spray dryer (DC1500) at a peristaltic pump feed rate of 3 mL / min, a nozzle spray temperature of 150 °C, and a discharge port temperature of 100 °C to obtain a heterojunction precursor. The heterojunction precursor was heated to 1400 °C within 10 s and subjected to Joule heat (YLJ-SPS-T20) shock for 10 min. Argon was used as the protective atmosphere to obtain a boron-fluorine co-doped cerium titanate-titanium niobate heterojunction. (3) Add 0.4 g of polymethyl methacrylate to the heterojunction material, and high-energy ball mill at a speed of 2500 r / min for 20 min to obtain a carbon-coated heterojunction precursor. In an argon protective atmosphere, heat the temperature to 500 °C at a rate of 3 °C / min and keep it at this temperature for 8 h to obtain a carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction, i.e., a negative electrode material for sodium ion batteries. Comparative Example 1
[0030] In this comparative example, Joule heat (YLJ-SPS-T20) shock was not used. Instead, a tubular furnace (GSL-1700X-HNG) was used to increase the temperature to 1600° C. at 3° C. / min and keep the temperature for 12 h. Other processes were consistent with those in Example 1. Comparative Example 2
[0031] In this comparative example, no boron fluoride compound or carbon source was added, and the other processes were the same as those in Example 1. Comparative Example 3
[0032] In this comparative example, no boron fluoride compound was added, and the other processes were the same as those in Example 1. Comparative Example 4
[0033] In this comparative example, no carbon source was added, and the other processes were the same as those in Example 1. Comparative Example 5
[0034] In this comparative example, no cerium titanate is added, that is, the operation of step (1) is not performed, and no cerium titanate is added in step (2). The other steps are consistent with the process of Example 1. Comparative Example 6
[0035] In this comparative example, steps (2) and (3) are not performed, that is, the material is the cerium titanate synthesized in step (1), and the rest of the process is the same as in Example 1.
[0036] The prepared carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction electrode was applied to sodium-ion batteries. The scraping method was selected, and the active material, acetylene black and PVDF were weighed in a mass ratio of 8:1:1. NMP was added and stirred into a viscous slurry. The slurry was scraped onto a copper foil and dried and cut into φ12 electrode sheets with a slicer. The sodium-ion batteries were assembled in a glove box and electrochemical tests were carried out after standing for 2 to 4 hours.
[0037] The above electrode sheet was used as the positive electrode, the negative electrode was metallic sodium, the diaphragm was GF / A glass fiber diaphragm, the electrolyte was 1mol / L sodium trifluoromethanesulfonate (NaCF3SO3), diethylene glycol dimethyl ether (DEGDME) was used as the solvent, and a CR2032 sodium ion battery was assembled for electrochemical testing. Constant current charge and discharge curve (GCD) test conditions: voltage window 0.001-2.5V, current density 0.3A / g, 0.5A / g, 1A / g, 2A / g, 5A / g. The capacity retention rate was tested by cycling 200 times at a current density of 0.5A / g.
[0038] The properties of the electrode materials obtained from the examples and comparative examples are summarized in Table 1 below.
[0039]
[0040] Figure 1 and Figure 2 C@BF-CeTi in Example 1 and Comparative Example 1 21 O 38 / TiNb2O7 material SEM spectrum, the matrix cerium titanate obtained in Example 1 is a spherical structure, and the niobium source and titanium source grow titanium niobate material on the spherical surface to obtain a heterojunction composite material with a sea urchin-like structure. Comparative Example 1 is a heterojunction composite material obtained by heating in an ordinary tubular furnace. During the heating process, due to the interface force and the electronegativity of BF ions, the needle-like structure grows irregularly, collapses, and agglomerates. Example 1 is heated quickly by Joule heat to avoid the influence of other ions, and the needle-like structure can be firmly attached to the spherical substrate to obtain a complete sea urchin-like composite material.
[0041] Figure 3 C@BF-CeTi prepared in Example 1 and Comparative Example 1 21 O 38 XRD spectrum of CeTi / TiNb2O7 materials, 21 O 38 The material has strong diffraction peaks at 2θ=21.06°, 24.39°, 30.83°, and 40.79°. The characteristic peaks and diffraction peaks at other angles are similar to those of CeTi. 21 O 38 The results of the standard card correspond to the successful synthesis of CeTi 21 O 38 Materials; The characteristic peaks of the XRD spectrum of the TiNb2O7 material also correspond to the standard card. From the XRD spectrum of the material in Example 1, it can be seen that the diffraction angles corresponding to (301), (202), and (-110) of TiNb2O7 are shifted to the right. From the Bragg equation, it can be seen that the interplanar spacing corresponding to this crystal plane is reduced, indicating that the BF ions are uniformly doped into the oxygen vacancies of the material; the opposite result appeared in Comparative Example 1, indicating that during the calcination process in the tubular furnace, the doped ions replaced the oxygen vacancies, causing structural distortion, and the corresponding interplanar spacing became larger.
[0042] Figure 4 and Figure 5 C@BF-CeTi prepared in Example 1 21 O 38 TEM and HRTEM spectra of / TiNb2O7 materials. It can be seen from the spectra that the carbon material is evenly covered on the surface of the heterojunction material. The lattice fringes of the selected internal heterojunction composite material are measured to be 0.34nm, corresponding to the (-110) crystal plane of titanium niobate in the composite material (theoretical value is 0.37nm). The test results correspond to the XRD results, indicating that BF ions are successfully doped into the material.
[0043] Figure 6 They are respectively C@BF-CeTi in Example 1 21 O 38The capacity retention rate and coulombic efficiency curve of TiNb2O7 material after 200 cycles at a current density of 0.5A / g is shown in Figure 2. Figure 6 From Table 1, it can be found that the specific capacity of the material in Example 1 at a current density of 0.3A / g is 312.44 mAh / g. With the increase of current density, the specific capacity shows a trend of gradually decreasing, and the specific capacity is 144.24 mAh / g at a current density of 5A / g. The capacity retention rate after 200 cycles at a current density of 0.5A / g is 88.93%, which has excellent cycle stability.
[0044] From the data in Table 1, we can find that compared with the performance of Comparative Examples 1-6, C@BF-CeTi 21 O 38 / TiNb2O7 materials have improved their specific capacities, with a capacity retention rate of 84-88%. The formation of a heterojunction can reduce the energy barrier of the material. With the doping of boron and fluorine ions, the interplanar spacing of the material is reduced, forming a built-in electric field, thereby improving the rate performance of the battery; after carbon is evenly coated on the outer layer of the material, it can reduce volume expansion, improve the reaction between the material surface and the electrolyte ions, and increase the cycle stability. It can be seen from Table 1 that when the amount of sodium fluoroborate added is 1g and the amount of polymethyl methacrylate added is 0.2g, the battery performance is optimal. The above results show that C@BF-CeTi 21 O 38 / TiNb2O7 material has excellent electrochemical performance and cycle stability in sodium battery anode.
[0045] The technical features of the above-described embodiments can be combined arbitrarily. To make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above implementation case description can be used to help understand the principles and methods of the present invention. However, the above implementation case is not unique and should not be construed as a limitation of the present invention. At the same time, for those of ordinary skill in the art, according to the principles and methods of the present invention, flexible changes can be made in specific implementation methods and application scopes.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: (1) mixing a cerium source, a titanium source and a polar solvent, ball milling, drying and calcining at high temperature to obtain cerium titanate; (2) mixing the cerium titanate, boron fluoride compound, titanium source, niobium source and alcohol organic solvent obtained in step (1), spray drying to obtain a heterojunction precursor, and subjecting the heterojunction precursor to Joule thermal shock to obtain a boron-fluorine co-doped cerium titanate-titanium niobate heterojunction; (3) adding a carbon source to the boron-fluorine co-doped cerium titanate-titanium niobate heterojunction obtained in step (2), ball milling to obtain a carbon-coated heterojunction precursor, and calcining under a protective atmosphere to obtain a carbon-coated boron-fluorine co-doped cerium titanate-titanium niobate heterojunction, i.e., a negative electrode material for a sodium ion battery.
2. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: In the step (1), the cerium source is one of cerium oxide, cerium acetate, and cerium trichloride; the concentration of the cerium source in the polar solvent is 1-2 mol / L; the titanium source is one of titanium dioxide, titanium isopropoxide, and tetrabutyl titanate; the polar solvent is one of methanol, ethanol, and deionized water; and the molar ratio of the cerium source to the titanium source is 1:2-3.
3. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: In the step (1), the ball milling speed is 300-700 r / min, and the ball milling time is 10-18 h; the drying temperature is 80-120° C., and the time is 10-16 h; the high-temperature calcination is carried out by controlling the heating rate of 3-10° C. / min to increase the temperature to 900-1450° C., and the insulation time is 12-20 h.
4. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: In the step (2), the titanium source is one of tetrabutyl titanate, isopropyl titanate, and titanium tetrachloride; the concentration of the titanium source in the alcohol organic solvent is 0.16-0.5 mol / L; the niobium source is one of niobium oxalate, niobium pentachloride, and niobium n-propoxide; the alcohol organic solvent is one of ethanol, methanol, and ethylene glycol; the molar ratio of cerium titanate to titanium niobate is 0.01-0.1:1; the boron fluoride compound is any one of sodium fluoroborate, ammonium fluoroborate, and zinc fluoroborate; and the molar ratio of the boron fluoride compound to titanium niobate is 0.1-1:
1.
5. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: In the step (2), the spray drying feed rate is 3-10 mL / min, the temperature is 150-200° C., and the discharge port temperature is 80-100° C.
6. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: In the step (2), the Joule thermal shock is to raise the temperature to 1200-1600° C. within 10-20 seconds under an argon or nitrogen protective gas atmosphere and keep the temperature for 5-10 minutes.
7. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: In the step (3), the carbon source is one of glucose, starch and polymethyl methacrylate; the molar ratio of the carbon source to titanium niobate is 0.8-2.1:1; the ball milling speed is 1500-2500 r / min, and the ball milling time is 10-30 min; the calcination is carried out under an argon or nitrogen protective gas atmosphere at a heating rate of 2-5°C / min to 500-800°C, and the holding time is 6-12 h.
8. An application of a sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The sodium ion battery negative electrode material is applied to a sodium ion battery.
Citation Information
Patent Citations
Preparation method of electrode material
CN106784773A
Sodium-ion battery nanosheet negative electrode material as well as preparation method and application thereof
CN114242995A
Sodium ion battery negative electrode material and preparation method thereof
CN117550638A
Niobate and niobate composite material and application of niobate composite material to secondary lithium battery
CN102760876A
Sodium ion battery negative pole active substance and preparation method and application thereof
CN103066265A
Cited By
Nanostructure-based lithium ion battery negative electrode material and preparation method thereof
CN121528890A